GAMBARAN PENGETAHUAN IBU TENTANG PENURUNAN NYERI PERSALINAN MENGGUNAKAN TEKNIK NAPAS DALAM - Rina Astuti; Sri Legawati (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Deep breathing technique is one type of breathing technique, and can reduce pain in mothers in labor non-pharmacologically by taking a deep breath during contractions using diaphragmatic breathing through the nose so that the abdomen is lifted slowly, the chest expands fully will flow oxygen to the blood which is then distributed throughout the body will release endorphin hormones which are natural pain relievers in the body. This study uses a